Mega-city construction engineering to residential satisfaction: new insights from Yan’ an of China - Huang, Huan; Qian, Xin-Meng; Xiao, Yi; Luo, Zi-Xin (Frontiers in Public Health, 2023)
The contradiction among population, economy and urbanization has gradually intensified, and the Mountain Excavation and City Construction (MECC) project is one of the special solutions. Nevertheless, there are few comparative studies on the project index studies and effect of MECC projects on residential satisfaction. To remedy this deficiency, this study base on the Yan'an new district (YND) reconstruction project, attempting to analyze the specific influencing factors pre-relocation and post-relocation from the perspective of residential satisfaction. The results show that the residential satisfaction index of the YND is indeed higher than that of the Yan'an old district (YOD) through t-test and age group regression analysis. Concurrently, the decisive factors of residential satisfaction are also different. Specifically, the interpersonal communication, supporting facilities, community environment and economic income are significant in the YOD, but only the aspect of supporting facilities is negative significant. The supporting facilities, community environment, economic income and urban development are all positive significant in the YND. The satisfaction factors of middle-aged people in YOD and YND have the most significant differences, and the significance of each dimension is different. The research results of this study provide a comparative perspective at the micro-level for evaluating China's urban construction, and it supplies specific directions for future urban development and the improvement of old cities through the new residential satisfaction index.